The influence of the video assistant referee (VAR) on the UEFA European Football Championship - Bao, R.; Li, Y. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: With the rapid development and enhancement of sport technology, a variety of high-tech auxiliary devices have gradually been introduced into football. The Video Assistant Referee (VAR) was officially introduced at the 2020 UEFA European Football Championship in order to assist referees in officiating the match. The aim of this study is to explore the influence of the introduction of VAR on the UEFA European Football Championship. METHODS: The match sample includes all 51 matches played in the 2016 UEFA European Football Championship without VAR and all 51 matches played in the 2020 UEFA European Football Championship with VAR. The following nine match performance variables were recorded for each match: the first-half match time, the second-half match time, total match time, offsides, fouls, yellow cards, red cards, goals and penalties. All the match statistics were retrieved from the UEFA official website (www.uefa.com). The statistical significance was set at p < 0.05. An independent sample T-test was first conducted to compare the difference between the variables with and without VAR. Subsequently, a mixed linear model (MLM) was used to clarify intra-tournament variations and control the random effects. RESULTS: The results demonstrated that after the introduction of VAR, there were significant increases in the 1st match time [p < 0.001, Cohen`s d = *0.335, 95%CI (*0.498, *0.272)], the 2st match time [p < 0.001, Cohen`s d = *0.233, 95%CI (*0.506, *0.107)], total match time [p < 0.001, Cohen`s d = *0.366, 95%CI (*0.689, *0.61)] and the number of penalties [p < 0.001, Cohen`s d = *0.282, 95%CI (*0.395, *0.06)]. In comparison, a significant decrease was observed in the number of offsides [p < 0.001, Cohen`s d = *0.456, 95%CI (0.211, 0.369)] after the introduction of VAR. In addition, the result of MLM found that the first-half match time (p < 0.01), the second-half match time (p < 0.01), total match time (p < 0.01), offsides (p < 0.01) and penalties (p < 0.01) were still significant after control for the random effects of the tournament period. CONCLUSION: The findings demonstrated significant increases in the first-half match time, second-half match time, total match time and the number of penalties. Furthermore, there was a significant reduction in the number of offsides after the introduction of VAR. In summary, this research may help football practitioners and fans better understand the influence of VAR on the worlds top professional football tournament., especially on the UEFA European Football Championship and also help to optimise referees` officiating strategies.